2012
DOI: 10.1002/jcp.24073
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 mediates the anti‐inflammatory effects during the granulocytic differentiation process in all‐trans retinoic acid‐treated acute promyelocytic leukemic cells

Abstract: Annexin A1 (AnxA1) originating from mature neutrophils and their microparticles (MPs) plays an important anti‐inflammatory role during the resolution phase of inflammation. However, the role of AnxA1 during the process of granulocytic differentiation is still unknown. All‐trans retinoic acid (ATRA) can induce acute promyelocytic leukemic (APL) cells to differentiate along the granulocytic lineage and has been used successfully in treating APL patients. In this study, we investigated whether or not AnxA1 contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…We confirmed that apo-MPs released during the apoptotic process differ phenotypically and quantitatively from those MPs released during cellular activation [20,21]. Recent studies indicate that MPs released by activated neutrophils or differentiated ATRA-APL cells are associated with anti-inflammatory property in which the anti-inflammatory mediator annexin A1 is involved [15,16,22]. In contrast to these studies, we demonstrate that apo-MPs released by apoptotic ATRA-NB4 cells induced a higher pro-transmigratory activity on NR8383 cells than those MPs released by living ATRA-NB4 cells (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We confirmed that apo-MPs released during the apoptotic process differ phenotypically and quantitatively from those MPs released during cellular activation [20,21]. Recent studies indicate that MPs released by activated neutrophils or differentiated ATRA-APL cells are associated with anti-inflammatory property in which the anti-inflammatory mediator annexin A1 is involved [15,16,22]. In contrast to these studies, we demonstrate that apo-MPs released by apoptotic ATRA-NB4 cells induced a higher pro-transmigratory activity on NR8383 cells than those MPs released by living ATRA-NB4 cells (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…The flow-cytometric analysis of the MP preparations showed the expected heterogeneous populations, with sizes varying approximately between 0.1 and 2µm as verified by the use of control beads (2-µm each; ACBP-20-10; Becton Dickson). The numbers of MPs within the same gated area of MPs in the flow cytometry dot plots, as shown in Figure 3A, were then calculated [15,16]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations